The impact of home country institutions on new venture export: examining new ventures in transition economies - Lee, M.; Yin, X.; Lee, S.; Weng, D.; Peng, Mike (2014)
How do home country institutions influence new ventures’ export strategy? As informed by the institution-based view, we argue that new ventures can use export to avoid the high costs of doing business in a home country with hostile institutions. Specifically, we argue that new ventures will export more when (1) their home countries have more government corruption problems, (2) managers have to spend more time with government officials for accessing public services, and (3) the proportion of ownership owned by foreign companies is high. Using a sample of 719 new ventures in 25 transition economies in Central and Eastern Europe (CEE), we find supportive results. We conclude that new ventures’ export strategy is tied to the costs of doing business in their home country institutions.